THE DILEMMA OF POLITICAL EDUCATION AS A TRANSFORMATION BASIS OF JEMAAH TARBIYAH MOVEMENT - Nasiwan Nasiwan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
This research aims at finding out the dilemma occurring in the political education, performed by the organization named Gerakan Jemaah Tarbiyah. A qualitative approach by critical analysis was employed, and the data was gathered by documented and in depth interview methods. The result explained that; first, political education in a phase of the missionary movement could influence Jemaah Tarbiyah in transforming the movement by transmitting various knowledge, attitude and political awareness that Jemaah Tarbiyah had. Second, there was a political education trend which already shifted the roles as the indoctrination instruments for the party to transmit values and justifier various policies decided by the elite of the party.